Manajamen Produksi Berita Pada Rubrik Kasus Dan Peristiwa Media Online Bengkuluekspress.Com - Azhar, Rajman; Narti, Sri; Yanto, Yanto (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
Of the many sections managed in the Bengkuluekspress.com online media, one of them is the Cases and Events section. This rubric contains news about events, laws and crimes in Bengkulu Province. The purpose of this research is to find out how News Production Management in the Case and Crime Rubric of Bengkuluekspress.com Online Media is able to survive and compete with other local news portals. This research uses descriptive qualitative research methods, by collecting data in the form of interviews with the leadership and editorial team of Bengkuluekspress.com and making direct observations to the field. This research uses the theory of the application of 4 management functions known as POAC, namely planning, organizing, actuating, and controlling. The results shown in this study show that Bengkuluekspress.com has implemented the POAC management function, but not maximally. In planning news production, a projection meeting has been held or determining the news to be published, but it is not consistent. In the application of management functions in organizing and mobilizing, the number of employees is limited, especially journalists filling the legal and criminal sections and editors who specifically handle these sections. Thus, Bengkuluekspress.com needs to add personnel or human resources in order to improve performance effectiveness and improve the quality of reporting. Then, based on the findings of data analysis, it can be concluded that News Production Management in the Case and Event Rubric of Bengkuluekspress.com is basically the same as news production management in other rubrics. There is only a slight difference for news events that cannot be planned for coverage. The news production planning process has been running quite well through editorial meetings to organize, calculate, prepare and formulate the implementation of activities.